Embodiment and Emotional Memory in First vs. Second Language - Baumeister, Jenny C.; Foroni, Francesco; Conrad, Markus; Rumiati, Raffaella I.; Winkielman, Piotr (Frontiers in Psychology, 2017)
Language and emotions are closely linked. However, previous research suggests that this link is stronger in a native language (L1) than in a second language (L2) that had been learned later in life. The present study investigates whether such reduced emotionality in L2 is reflected in changes in emotional memory and embodied responses to L2 in comparison to L1. Late Spanish/English bilinguals performed a memory task involving an encoding and a surprise retrieval phase. Facial motor resonance and skin conductance (SC) responses were recorded during encoding. The results give first indications that the enhanced memory for emotional vs. neutral content (EEM effect) is stronger in L1 and less present in L2. Furthermore, the results give partial support for decreased facial motor resonance and SC responses to emotional words in L2 as compared to L1. These findings suggest that embodied knowledge involved in emotional memory is associated to increased affective encoding and retrieval of L1 compared to L2.